Lupus-Like Syndrome During Anti TNF-Alpha Therapy: A Case Report - Özlem Altındağ,; Ali Aydeniz,; Savaş Gürsoy,; Erman Yağız,; İrfan Koca, (Archives of Rheumatology, 2008)
Anti TNF-α therapy is considered as an important progress in the treatment of rheumatoid arthritis by slowing joint erosions and improving physical function. Patients treated with this therapy raised concerns for development of systemic autoimmune diseases such as systemic lupus erythematosus (SLE). Although new autoantibody formation is common with anti-TNF therapy, there are only rare reports of SLE, In this case report, we presented a 45-year-old woman who developed SLE under etanercept treatment. Etanercept induced lupus syndrome must be kept in mind in the presence of clinical findings suggestive of SLE in patients with rheumatoid arthritis. (Rheumatism 2008; 23: 154-6)